PENGARUH INTENSITAS PENGUNAAN GADGET DAN KEIKUTSERTAAN TPA TERHADAP KEMAMPUAN MEMBACA AL-QURAN - Khoirul Anisa; Retno Wahyuningsih (Islamic Management: Jurnal Manajemen Pendidikan Islam, 2021)
This study aims to determine (1) the effect of the intensity of using gadget  on the ability recite  Qur’an, (2) the effect of TPA participation on the ability recite  Qur’an, (3 ) the effect of the intensity of using gadget  and TPA participation on the ability recite  Qur’an. The study was conducted in 2020. The population is fifth grade students of SD Negeri Cluster II Ahmad Yani Laweyan Surakarta on academic years of 2020/2021. The samples were drawn randomly from the population using a stratified random sampling technique. The study used experimental methods. The data were analyzed using two - way analysis of variance and further test of data processing with software SPSS 22 For Windows. The results showed that the highest average score was students who had low intensity of using gadget  and participated in TPA (89.467) and the lowest score was students who had low intensity of using gadget  and did not attend TPA (58.5). This proves that the higher the use of gadget s and the more active students are in participating in the TPA, the higher the ability recite  Qur’an. So, it can be concluded (1) The intensity of using gadget  did not affect the students' ability to read Al-Quran, (2) TPA participation affected the ability recite  Qur’an, (3) The intensity of using gadget  and TPA participation affected the ability recite Al-Quran.Keywords: gadget, participation, ability